PENERAPAN K3 KONSTRUKSI DENGAN MENGGUNAKAN METODE HIRARC PADA PEKERJAAN AKSES JALAN MASUK (STUDI KASUS : JL. PROF. DR. H. HADARI NAWAWI) - Rifani, Yuda; Mulyani, Endang; Pratiwi, Riyanny (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
â€œKeselamatan dan Kesehatan Kerjaâ€ (K3) is an effort to overcome potential hazards or health and health risks that may occur. Occupational Safety Risk is still commonly overlooked. The construction service industry is one of the industrial sectors that has the risk of work accident. Frequent occurrence of work accidents on construction projects caused less attention K3.In research and this final project will be examined about the implementation of K3 on construction project. The first thing to do is to identify what K3 risks are likely to occur in building construction work and analysis of those risks. The risk analysis is to know the risk of K3 most common in building construction work based on the result of questionnaires distributed to respondents who work on building construction work. The risk of K3 will be analyzed by using HIRARC (Hazard Identification, Risk Assessment & Risk Control) method. Furthermore, we will conduct risk control to provide solutions to the health and safety risks that have been analyzed.In this study, the highest risk for workers is the activity of mobilization of heavy equipment on new building construction by using wheel truck > 8 can squeeze or crash the worker who work on road access with value 15,10. While the highest risk for non-workers is heavy equipment mobilization activity using wheel truck > 8 and material mobilization using wheel truck <8 on new building construction with risk can squeeze or crash non-worker who is passing in access road with value 14,60 and 11.18.Based on the analysis, the risk control alternatives are made to minimize the possible health and safety risks in the access of building road and the building infrastructure among others: to prepare the security officer to perform the escort during the mobilization of equipment, schedule the mobilization activities of the equipment and materials, safety barriers, road barriers, traffic cones, mounting signs, providing APD (Alat Pelindung Diri) for workers, providing counseling to workers to be vigilant when doing roadside activities, around excavated pits or borders, providing adequate lighting , providing special heavy vehicle parking locations, providing security officers / supervisors when heavy equipment operates and also when loading material unloaded with dump truck, clean the material entering the road area periodically.Â Keywords: Implementation of â€œKeselamatan dan Kesehatan Kerjaâ€ (K3), HIRARC, Work Accident